Rab-mediated trafficking in the secondary cells of Drosophila male accessory glands and its role in fecundity - Prince, E; Kroeger, B; Gligorov, D; Wilson, C; Eaton, S; Karch, F; Brankatschk, M; Maeda, R (Wiley, 2018)
The male seminal fluid contains factors that affect female post‐mating behavior and physiology. In Drosophila, most of these factors are secreted by the two epithelial cell types that make up the male accessory gland: the main and secondary cells. Although secondary cells represent only ~4% of the cells of the accessory gland, their contribution to the male seminal fluid is essential for sustaining the female post‐mating response. To better understand the function of the secondary cells, we investigated their molecular organization, particularly with respect to the intracellular membrane transport machinery. We determined that large vacuole‐like structures found in the secondary cells are trafficking hubs labeled by Rab6, 7, 11 and 19. Furthermore, these organelles require Rab6 for their formation and many are essential in the process of creating the long‐term postmating behavior of females. In order to better serve the intracellular membrane and protein trafficking communities, we have created a searchable, online, open‐access imaging resource to display our complete findings regarding Rab localization in the accessory gland.